QTL Mapping of a High Protein Digestibility Trait in Sorghum bicolor. (28th May 2009) - Winn, Jennifer A.; Mason, R. Esten; Robbins, Adriana L.; Rooney, William L.; Hays, Dirk B.
Abstract : Compared with other cereal grains, Sorghum bicolor shows lower protein digestibility. The low digestibility is thought to result from disulfide cross linking in theβ - andγ -kafirins. In contrast, the single recessive high digestibility/high lysine content (HD) mutation which confers greater grain digestibility exists in sorghum that is thought to result from reduced accumulation ofγ -kafirin that allows greater access to the high digestibleα -kafarin fraction. In an effort to both clearly define the molecular basis for the HD trait and develop tools to improve the introgression of this difficult-to-screen trait, this study focuses on mapping the QTLs linked to this trait. While the HD trait has been defined as a single recessive gene, our results uncovered that two major QTLs on chromosome 1 are associated with protein digestibility—one QTL (locus 1 from the HD parent) unfavorably affects digestibility and one QTL (locus 2 from the HD parent) only 20 cM away favorably affects digestibility. A contrast analysis between genotypic groups at these two loci shows that a higher level of protein digestibility may be obtained when this linkage in repulsion is broken and favorable alleles are allowed to recombine.